2009
DOI: 10.3899/jrheum.080615
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor-α −308 Genotypes Influence Inflammatory Activity and TNF-α Serum Concentrations in Children with Juvenile Idiopathic Arthritis

Abstract: TNF-alpha -308 GA/AA genotypes were found to be related to higher inflammatory activity and worse measures of disease activity in Portuguese patients with JIA. They were not associated with susceptibility to JIA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 30 publications
2
14
0
Order By: Relevance
“…Of interest, we found higher, though not signiWcantly, serum TNF levels in SLE patients carrying the A allele, which may have contributed to the observed higher disease activity and greater prevalence of lupus nephritis. These results are in accordance with previous studies of Portuguese patients with inXammatory rheumatic diseases, which found the TNF promoter polymorphism at position -308 to inXuence rheumatoid arthritis activity and severity [26], juvenile idiopathic arthritis inXammatory activity [27], and also some clinical features of ankylosing spondylitis [28], but not to inXuence the susceptibility to these diseases. The contribution of the LTA gene polymorphism at position 252 to SLE susceptibility has been reported mainly in Asian populations [12][13][14].…”
Section: Was Reported In European Patients With Sle and A Meta-analyssupporting
confidence: 94%
“…Of interest, we found higher, though not signiWcantly, serum TNF levels in SLE patients carrying the A allele, which may have contributed to the observed higher disease activity and greater prevalence of lupus nephritis. These results are in accordance with previous studies of Portuguese patients with inXammatory rheumatic diseases, which found the TNF promoter polymorphism at position -308 to inXuence rheumatoid arthritis activity and severity [26], juvenile idiopathic arthritis inXammatory activity [27], and also some clinical features of ankylosing spondylitis [28], but not to inXuence the susceptibility to these diseases. The contribution of the LTA gene polymorphism at position 252 to SLE susceptibility has been reported mainly in Asian populations [12][13][14].…”
Section: Was Reported In European Patients With Sle and A Meta-analyssupporting
confidence: 94%
“…Follow-up ranged from 6 months to as much as 23 years. In total, 6 out of 15 studies were prospective cohort studies36 43–45 49 50 and one was a cross-sectional study,51 which assessed genetic predictors only.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have focused blood and synovial cytokine polymorphisms; a major involved cytokine in JIA is the TNF- α ; the polymorphisms of its gene have been evaluated in different studies to establish its role in the pathogenesis and in the therapeutic response to anti-TNF- α drugs [4, 6, 7, 35, 36]. …”
Section: Resultsmentioning
confidence: 99%
“…The role of −308A/G polymorphism in JIA was investigated in many studies. Some authors found that the A allele was significantly more frequent in JIA subjects with respect to controls and was related to a higher disease activity [36] and a poor prognosis [43, 74]. Zeggini et al showed that the TNF −308A allele is more frequently found in rheumatoid factor positive juvenile polyarthritis and is associated with a more severe disease, while the more common TNF −308G allele may be protective [13].…”
Section: Resultsmentioning
confidence: 99%